Relationships between foreign direct investment and official development assistance with trade-related illicit financial flows. Evidence from low- and middle-income countries - Ortega-Aguaza, Bienvenido; Sanjuán-Solís, Jesús Carlos (Emerald, 2023)
Purpose This paper aims to analyse empirically the association between flows of foreign direct investment (FDI), net official development assistance (ODA) inflows and trade-related illicit financial outflows. Design/methodology/approach With this purpose, a linear model was estimated, using different panel-data estimators, and using a database for a sample of 49 countries spanning the period 2008–2017. The used measure of illicit financial outflows was based on the estimates by Global Financial Integrity of deliberate misinvoicing in merchandise trade. Findings Research findings show a significant and positive association between changes in both relative lagged net FDI flows and relative FDI outflows (as % of gross domestic product) and changes in the ratio of trade-related illicit capital outflows to total trade. However, these positive associations were only observed in the case of low-income countries. Also, the positive association of net ODA inflows on the IFFT outflows were restricted to the cluster of lower-middle-income countries. Originality/value To the best of the authors’ knowledge, this is one of the first studies to empirically estimate the association between FDI and ODA flows and trade misinvoicing at a macroeconomic level. Research findings may contribute to substantiate the concerns expressed in previous research about the potential unintended effects of aid on illicit capital flight in the case of lower-middle-income countries. They also shown that FDI flows could be an additional conduit for trade-related illicit financial flows in these countries
Keywords: Inversiones extranjeras; Comercio de mercancias; Foreign direct investment; Illicit financial flows; Low- and middle-income countries; Official development assistance; Trade